2012
DOI: 10.1091/mbc.e11-12-1059
|View full text |Cite
|
Sign up to set email alerts
|

Multiple repeat elements within the FAM21 tail link the WASH actin regulatory complex to the retromer

Abstract: The WASH complex controls actin dynamics on endosomes, and its functional mechanism is poorly defined. The WASH complex subunit Fam21 bears many copies of a novel motif that directly interacts with the retromer cargo-selective complex. Endosomal localization of FAM21 requires both the retromer and multivalency of the repeat elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
258
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(278 citation statements)
references
References 38 publications
17
258
1
2
Order By: Relevance
“…WASH localizes to endosomes (Derivery et al, 2009;Gomez and Billadeau, 2009;Harbour et al, 2012;Jia et al, 2012;Monfregola et al, 2010;Monteiro et al, 2013;Ryder et al, 2013), and WASHgenerated F-actin not only regulates the architecture of the endolysosomal system, but also spares specific cargo from lysosomal degradation or missorting (Bartuzi et al, 2016;Derivery et al, 2009Derivery et al, , 2012Duleh and Welch, 2010;Gomez and Billadeau, 2009;Gomez et al, 2012;Monteiro et al, 2013;Zech et al, 2011). WASH is recruited to retromer-positive endosomal subdomains via the interaction of the extended C-terminal tail of FAM21 with the retromer subunit VPS35 (Harbour et al, 2012;Jia et al, 2012).…”
Section: Jmymentioning
confidence: 99%
See 1 more Smart Citation
“…WASH localizes to endosomes (Derivery et al, 2009;Gomez and Billadeau, 2009;Harbour et al, 2012;Jia et al, 2012;Monfregola et al, 2010;Monteiro et al, 2013;Ryder et al, 2013), and WASHgenerated F-actin not only regulates the architecture of the endolysosomal system, but also spares specific cargo from lysosomal degradation or missorting (Bartuzi et al, 2016;Derivery et al, 2009Derivery et al, , 2012Duleh and Welch, 2010;Gomez and Billadeau, 2009;Gomez et al, 2012;Monteiro et al, 2013;Zech et al, 2011). WASH is recruited to retromer-positive endosomal subdomains via the interaction of the extended C-terminal tail of FAM21 with the retromer subunit VPS35 (Harbour et al, 2012;Jia et al, 2012).…”
Section: Jmymentioning
confidence: 99%
“…WASH is recruited to retromer-positive endosomal subdomains via the interaction of the extended C-terminal tail of FAM21 with the retromer subunit VPS35 (Harbour et al, 2012;Jia et al, 2012). Interestingly, a mutation in VPS35 (D620N) (Vilariño-Güell et al, 2011;Zimprich et al, 2011) that is associated with earlyonset Parkinson's disease has been shown to diminish the interaction of the SHRC with VPS35 and impair vesicular trafficking from the late endosome (Follett et al, 2013;McGough et al, 2014;Zavodszky et al, 2014).…”
Section: Jmymentioning
confidence: 99%
“…The WASH complex also directly interacts with the retromer sorting complex and is thus required for the specific retrieval of retromer cargos from several endocytic compartments (23,32).…”
Section: Significancementioning
confidence: 99%
“…2C). Indeed, phagosomal acidification was actually slightly decreased, most likely due to decreased V-ATPase supply, as so much is sequestered in later compartments such as postlysosomes (27,30 mammalian cells, WASH mediates sorting from endosomes via direct interaction between the FAM21 subunit of the WASH complex and the VPS35 subunit of the retromer sorting complex (24,32,36). The retromer complex drives extraction of specific proteins at several trafficking steps by sequence-specific binding (37)(38)(39).…”
Section: Wash Is Recruited To Early Macropinosomes and Phagosomesmentioning
confidence: 99%
“…Furthermore, silencing of CCDC93 or C16orf62 (two additional components of the CCC complex) also led to reduced plasma membrane staining for Notch2, a pattern also observed on silencing of VPS35 (Fig. S3, A and B), a subunit of the retromer complex which is important for WASH recruitment and function (Harbour et al, 2012;Jia et al, 2012). Altogether, these findings indicate that the absence of COM MD9 and associated factors results in the accumulation of Notch2 in the early endosomal compartment.…”
Section: Com Md9 and The CCC And Retromer Complexes Regulate Surfacementioning
confidence: 52%